2009
DOI: 10.1007/s11671-009-9363-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Field Emission from Argon Plasma-Treated Ultra-sharp α-Fe2O3Nanoflakes

Abstract: Hematite nanoflakes have been synthesized by a simple heat oxide method and further treated by Argon plasmas. The effects of Argon plasma on the morphology and crystal structures of nanoflakes were investigated. Significant enhancement of field-induced electron emission from the plasma-treated nanoflakes was observed. The transmission electron microscopy investigation shows that the plasma treatment effectively removes amorphous coating and creates plenty of sub-tips at the surface of the nanoflakes, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…We proposed that the plasma plays the key role for the diamond transition from various carbon modifications. Based on the theory of plasma physics, the gases like H 2 , Ar, O 2 , and so on can be used as plasma generating gases which can enhance the plasmas generation (Zheng et al, 2009). Therefore, in this study, the effect of the atmosphere on the diamond growth in the SPS was studied.…”
Section: Effect Of Atmospheres On the Diamond Growth In The Spsmentioning
confidence: 99%
“…We proposed that the plasma plays the key role for the diamond transition from various carbon modifications. Based on the theory of plasma physics, the gases like H 2 , Ar, O 2 , and so on can be used as plasma generating gases which can enhance the plasmas generation (Zheng et al, 2009). Therefore, in this study, the effect of the atmosphere on the diamond growth in the SPS was studied.…”
Section: Effect Of Atmospheres On the Diamond Growth In The Spsmentioning
confidence: 99%
“…Excellent field emission performance including low turn-on field, high current density, good stability, and high uniformity has been reported for various one-dimensional a-Fe 2 O 3 nanomaterials. [13][14][15][16][17][18][19][20] For example, Zhu et al reported that high field emission current density of 1.6 A/cm 2 could be obtained from a-Fe 2 O 3 nanoflakes which were prepared on atomic force microscope tip. 13 In 2011, Lu et al reported the field emission properties of a-Fe 2 O 3 nanowires and low turn-on field of 1.7 MV/m was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Ar plasma treatment could effectively clean the nanoflakes and create ultra-sharp sub-tips and consequently significantly enhance electron emission from plasma-treated nanoflakes. 16 Lu et al found that the field emission current density of a-Fe 2 O 3 nanowires could be enhanced dramatically by applying electric field to the field emitters repeatedly, which was attributed to oxygen molecules desorption from a-Fe 2 O 3 nanowires surface. 14 Besides excellent field emission properties, the compatibility of cold cathode in working environment should be carefully considered.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale protuberances reduce the diameter of the eld emitter and thereby increase the eld enhancement, which will enhance electron eld emission. 26,41 Therefore, the decrease in the threshold eld of the W 18 O 49 nanowires was observed when the irradiation dose increased to 3.6 Â 10 15 phs cm À2 .…”
Section: Resultsmentioning
confidence: 91%